Evaluation of Serum Copper, Zinc and Copper/Zinc Ratio in Psoriatic Patients - Modawe, GadAllah Osamn; Adam, Abuelhassan E.; Hobiel, Hafiz Ahmed; Ahmed, Suhair A.; Ismail, Amar Mohamed (Gezira Journal of Health Sciences, 2022)
Backgrounds: Psoriasis is a hyper proliferative coetaneous disease of multi-factorial etiologies, genetic background, environmental factors, vascular and immune system disturbances. Copper and zinc are very importance trace elements and essential to biochemical processes in the body and are involved in immunological and inflammatory reactions. Objective: The objective of the present study was to evaluate the relationship between zinc (Zn) and copper (Cu) ion and copper/zinc with the pathogenesis of psoriasis disease. Materials and Methods: an analytical case control hospital based study conducted in Khartoum dermatology and venerology teaching hospital, Khartoum state, Sudan. During the period from September to December 2018. A total of 100 subjects were enrolled in the study, 50 psoriatic patients as case group and 50 apparently healthy as control group with match age and sex. The age ranged from 12 and 60 years and their average mean 32 years. Three ml of venous blood were collected from each volunteer, serum was obtained and analyzed using colorimetric method in fully Automated Biochemistry Analyzer and the data was analyzed using SPSS version (21). P-value of <0.05 was considered significant . And also psoriatic patients the severity of psoriasis was assessed by ‘Psoriasis Area Severity Index’ (PASI score). Results: The study revealed a significantly increase (p = 0.000) of serum copper in psoriatic patients compared to control group and a significantly decrease (p = 0.040) of serum zinc in psoriatic patients compared to control group. And the copper/ zinc was significantly increase (p = 0.000) in patients than controls. Moreover, serum copper was  significantly increased (p = 0.012) in psoriatic patients infected >1 year compared to patients infected 6 months to 1 year. The serum zinc was significantly decreased (p = 0.030) in psoriatic patients infected >1 year compared to patients infected 6 month-1 year. And also the copper/ zinc significantly increased (p = 0.027) in psoriatic patients infected >1 year compared to patients infected 6 month to 1 year. The serum copper was a significantly different (p =0.001) between severity of psoriatic disease compared to mild and moderate. Moreover, the serum zinc was  significantly different (p =0.001) between mild and moderate and also a significantly different (p =0.022) between severity of psoriatic disease compared to mild and moderate. The copper/ zinc was a significantly different (p =0.000) between severity of psoriatic disease compared to mild and moderate. Conclusion: The psoriatic patients had a significantly increased serum copper, copper/ zinc and a significantly decrease of serum zinc. The study observed that, the common in male than female and also in moderate a stage of severity.